Spatio-temporal monitoring of coastal floating marine debris in the Balearic Islands from sea-cleaning boats. (April 2019) - Compa, Montserrat; March, David; Deudero, Salud
Abstract: Mismanaged waste is accumulating at an alarming rate in the marine environment. Its presence has caused local authorities in the Balearic Islands to develop a coastal sea-cleaning boat service covering the region, identifying the floating marine debris, and removing it from the coastal areas. This study considered daily monitoring from May to October spanning from 2005 to 2015. Plastic marine debris composed over 54% of all floating marine debris removed daily across the Balearic Islands. The spatio-temporal patterns indicate a heterogeneous distribution of plastic in the coastal areas, with higher concentrations in the north-western and south-eastern regions of the islands and debris peaking during the month of August. Furthermore, floating marine debris was more easily collected during calm seas as well as using an integrated monitoring approach to facilitate its removal. Overall, sea-cleaning boats are highly effective in removing coastal floating marine debris. Highlights: Sea-cleaning boat monitoring provides long-term information on the spatio-temporal trends of coastal marine debris. Marine debris collected from 2005 to 2015 ranged annually from 27 tonnes to over 100 tonnes. 54% the marine debris collected was plastic. An integrated approach increased marine debris collection in coastal areas. Spatial aggregation indicates low temporal variability in plastic debris but consistency in regional spatial abundance.